Predicting Cost‐Effectiveness of Generic vs. Brand Dabigatran Using Pharmacometric Estimates Among Patients with Atrial Fibrillation in the United States. Issue 2 (13th February 2020) - Wang, Ching‐Yu; Pham, Phuong N.; Kim, Sarah; Lingineni, Karthik; Schmidt, Stephan; Diaby, Vakaramoko; Brown, Joshua
Abstract : Generic entry of newer anticoagulants is expected to decrease the costs of atrial fibrillation management. However, when making switches between brand and generic medications, bioequivalence concerns are possible. The objectives of this study were to predict and compare the lifetime cost‐effectiveness of brand dabigatran with hypothetical future generics. Markov microsimulations were modified to predict the lifetime costs and quality‐adjusted life years of patients on either brand or generic dabigatran from a US private payer perspective. Event rates for generics were predicted using previously developed pharmacokinetic‐pharmacodynamic models. The analyses showed that generic dabigatran with lower‐than‐brand systemic exposure were dominant. Meanwhile, generic dabigatran with extremely high systemic exposure was not cost‐effective compared with the brand reference. Cost‐effectiveness of generic medications cannot always be assumed as shown in this example. Combined use of pharmacometric and pharmacoeconomic models can assist in decision making between brand and generic pharmacotherapies.